Clival Chordoma: Endoscopic Bilateral Transmaxillary Approach - Youssef, A. Samy; Yang, Alexander; Getz, Anne E.; Mizuho, Inoue; Labib, Mohamed (Journal of Neurological Surgery Part B: Skull Base, 2019)
We present a case of a large clival chordoma in a 54-year-old female with a past medical history of Turner's syndrome and a 1.5-year history of nasal congestion. The tumor was extending in the nasopharynx to both pterygopalatine fossae. An expanded endoscopic endonasal approach was selected. Stereotactic navigation was utilized. Bilateral transmaxillary approach with ethmoidectomy was performed, and a transclival corridor to the deepest portion of the tumor was created. The tumor was successfully dissected off the medial walls of the cavernous sinuses. Gross-macroscopic resection was achieved. Surgical reconstruction of the skull base comprised of a fat graft, fascia lata overlay, and dural sealant. Given the extensive nasal involvement by the tumor, a vascularized nasoseptal flap was not feasible. The patient had an unremarkable postoperative course. She underwent intensity-modulated radiation therapy (IMRT) radiotherapy 6 weeks later, and was seen in follow-up 6 months later, with no issues.The link to the video can be found at: https://youtu.be/4bnsEUtieAw.
Keywords: endoscopic endonasal; chordoma; clival; transmaxillary